2015
DOI: 10.1080/17441692.2015.1006241
|View full text |Cite
|
Sign up to set email alerts
|

Men's attitudes: A hindrance to the demand for voluntary medical male circumcision – A qualitative study in rural Mhondoro-Ngezi, Zimbabwe

Abstract: Male circumcision has witnessed a paradigm shift from being regarded as a religious and cultural practice to a global intervention strategy meant to curb transmission of HIV. This is particularly evident in sub-Saharan African countries where the HIV prevalence is greater than 15%. Zimbabwe adopted the voluntary medical male circumcision (VMMC) strategy in 2009; however, since then the uptake of the intervention has only 10% of the adult male population has reported having been circumcised. To better understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Our findings indicate that while messages about the biomedical value of VMMC were reported by study participants, these messages were sometimes mixed with beliefs drawn from traditional circumcision practices. Other research has shown the importance of understanding such long-held beliefs which influence the use and uptake of biomedical technology (Aggleton, 2007;Andersson et al, 2011;Moyo et al, 2015) as well as the importance of taking into account other community member views, including the views of men's sexual partners in order to support VMMCa finding also illustrated in recent work in Zambia (Cook et al, 2015;Riess et al, 2014) Uganda (Gilliam et al, 2010) and northern Tanzania (Osaki et al, 2015). In settings with mixed ethnic groups, such as the fishing communities where this study was set, the messages about the purpose of VMMC, and the procedures to follow to promote healing, compete with beliefs which promote unsafe behaviour (Kamath & Limaye, 2015;Toefy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings indicate that while messages about the biomedical value of VMMC were reported by study participants, these messages were sometimes mixed with beliefs drawn from traditional circumcision practices. Other research has shown the importance of understanding such long-held beliefs which influence the use and uptake of biomedical technology (Aggleton, 2007;Andersson et al, 2011;Moyo et al, 2015) as well as the importance of taking into account other community member views, including the views of men's sexual partners in order to support VMMCa finding also illustrated in recent work in Zambia (Cook et al, 2015;Riess et al, 2014) Uganda (Gilliam et al, 2010) and northern Tanzania (Osaki et al, 2015). In settings with mixed ethnic groups, such as the fishing communities where this study was set, the messages about the purpose of VMMC, and the procedures to follow to promote healing, compete with beliefs which promote unsafe behaviour (Kamath & Limaye, 2015;Toefy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that the introduction of VMMC in societies where male circumcision is not part of religious or cultural practice has not been without challenges because of the association of the act with ethnic and religious identities (Ahlberg & Njoroge, 2013;Parkhurst, Chilongozi, & Hutchinson, 2015). In Zimbabwe, where the majority of ethnic groups do not practice circumcision, Hatzold and colleagues and Moyo and colleagues (Hatzold et al, 2014;Moyo, Mhloyi, Chevo, & Rusinga, 2015) describe the social and cultural barriers to introducing VMMC. In South Africa too, local concepts of ethnicity and identity have influenced the perceptions and uptake of VMMC (Khumalo-Sakutukwa et al, 2013;Vincent, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Adams and Moyer (2015) found that some Swazi men perceived circumcision as a threat to their masculinity due to perceived negative effects it could have on their sex lives (e.g., loss of sensitivity, inability to pleasure female partners). Moyo, Mhloyi, Chevo, and Rusinga (2015) and Khumalo-Sakutukwa et al (2013) found similar masculinity-related barriers to men's circumcision in their studies in Zimbabwe and South Africa, respectively.…”
Section: Introductionmentioning
confidence: 54%
“…In KwaZulu-Natal, South Africa it was found that VMMC is associated with perceptions of gender identity and masculinity including sexual performance, sexual image and self-identity (31). In Zimbabwe the perceived challenge to masculinity was one of the major barriers to acceptability and uptake of VMMC (32).…”
Section: Discussionmentioning
confidence: 99%